Pandemic-related experiences, mental health symptoms, substance use, and relationship conflict among older adolescents and young adults from Manitoba, Canada. (May 2022) - Salmon, Samantha; Taillieu, Tamara L.; Fortier, Janique; Stewart-Tufescu, Ashley; Afifi, Tracie O.
Highlights: A large proportion of older adolescents and young adults reported increased feelings of stress/anxiety and depression, cannabis and alcohol use, and interpersonal conflict due to the COVID-19 pandemic. Females reported greater financial hardship, stress/anxiety, depression, and conflict with parents than males. Young adults reported greater financial hardship and feelings of depression than older adolescents. A higher household income was protective of alcohol consumption, conflict with parents, and a lack of emotional support during the pandemic. Abstract: There is growing awareness of the negative impact of the COVID-19 pandemic on young people. The purpose of this study was to examine older adolescents' and young adults' pandemic-related experiences, including financial difficulties, emotional support, social connections, mental health symptoms, substance use, and relationship conflict. Data from the Well-being and Experiences Study (The WE Study) were gathered from November to December 2020 in Manitoba, Canada, among a community sample ( n = 664; ages 16–21 years). Over half of the sample self-reported increased stress/anxiety (57.6%) and depression (54.2%) attributed to the pandemic. Increased alcohol consumption was reported by 18.2% of alcohol-users. Among cannabis-users, 35.1% reported increased use. Conflict with parents, siblings, and an intimate partner increased for 19.9%, 15.2%, and 24.0% of respondents, respectively. Females reported greater financial burden, mental health burden, and conflict with parents than males. Young adults reported greater financial and mental health burden than older adolescents. Higher household income was protective of some experiences. The current study adds to growing evidence that young people were adversely impacted by the COVID-19 pandemic. Increased access to virtual support resources is needed and should continue following the pandemic. Evidence-based interventions may need to be tailored to females and young adults.